(untitled) (LACCEI, 2024)
Due to the increase in the production of fruits for consumption and export, large amounts of waste from the same fruits are being generated, causing a great environmental problem, especially in developing countries that do not have an adequate process for their use or treatment. In this context, microbial fuel cells are presented as a novel technology that could provide a solution to this problem in the future by reusing organic waste as an energy source. In the present work, microbial fuel cells were manufactured on a laboratory scale using apple waste as a substrate with Zinc and Copper electrodes. It was possible to generate electrical current and voltage peaks of 7.567 ± .0117 mA and 1.452 ± 0.023 V, which operated with an electrical conductivity of the substrate of 152.326 ± 4.58 mS/cm and with an acid pH on day 16, where it was observed their maximum values. An internal resistance of approximately 31.548 ± 4.871 Ω was found, whose power density was 466.27 ± 16.824 mW/cm2 at a current density of 4.424 A/cm2. The microbial fuel cells were connected in series managing to generate a voltage of 3.17 V, enough to light a red LED light.